Design, modeling and simulation of perturb and observe maximum power point tracking for a photovoltaic water pumping system - Hilali, Abdelilah; Mardoude, Yahya; Ben Akka, Youssef; El Alami, Hassan; Rahali, Abderrafii (Institute of Advanced Engineering and Science, 2022)
Maximum power point tracking (MPPT) is considered one of the important factors in minimizing the installation costs and improving the efficiency of any photovoltaic water pumping system. The MPPT controller is specifically used to extract the maximum available power from the photovoltaic (PV) array. The maximum power can be achieved by using a specific algorithm. This work aims to raise awareness among farmers about the energy benefits available in the region of Meknes in Morocco, the economic gain and the environmental impact applied to the solar pumping system so that it can be generalized. To obtain the maximum power at each moment, a direct current (DC) water pump (SQF 0-6-2) powered by the solar panels (REC_330NP) through a buck converter was adapted. In addition, this study illustrates the theory of operation of the perturb and observe (P&O) algorithm and simulates the evaluation of this algorithm under different operating conditions (temperature and solar irradiation), and showed the advantages of this system that can operate at the optimal power regardless of disturbances.